Note: It seems the first term of your sequence is 7 instead of 2. So, I am assuming you meant the sequence such as;
7, 12, 17, 22, 27
Answer:
The expression for the nth term of the givens sequence is:
Step-by-step explanation:
Given the sequence
7, 12, 17, 22, 27
Here, the first element of the sequence is:
![a_1=7](https://tex.z-dn.net/?f=a_1%3D7)
An arithmetic sequence has a constant difference 'd' and is defined by
![a_n=a_1+\left(n-1\right)d](https://tex.z-dn.net/?f=a_n%3Da_1%2B%5Cleft%28n-1%5Cright%29d)
computing the differences of all the adjacent terms
![12-7=5,\:\quad \:17-12=5,\:\quad \:22-17=5,\:\quad \:27-22=5](https://tex.z-dn.net/?f=12-7%3D5%2C%5C%3A%5Cquad%20%5C%3A17-12%3D5%2C%5C%3A%5Cquad%20%5C%3A22-17%3D5%2C%5C%3A%5Cquad%20%5C%3A27-22%3D5)
The difference between all the adjacent terms is the same and equal to
![d=5](https://tex.z-dn.net/?f=d%3D5)
so substituting d = 5 and
in the nth term to determine the expression
![a_n=a_1+\left(n-1\right)d](https://tex.z-dn.net/?f=a_n%3Da_1%2B%5Cleft%28n-1%5Cright%29d)
![a_n=5\left(n-1\right)+7](https://tex.z-dn.net/?f=a_n%3D5%5Cleft%28n-1%5Cright%29%2B7)
![a_n=5n+2](https://tex.z-dn.net/?f=a_n%3D5n%2B2)
Therefore, the expression for the nth term of the givens sequence is: